The metabolic dysfunction of white adipose tissue induced in mice by a high-fat diet is abrogated by co-administration of docosahexaenoic acid and hydroxytyrosol. Issue 10 (7th October 2020) - Illesca, Paola; Valenzuela, Rodrigo; Espinosa, Alejandra; Echeverría, Francisca; Soto-Alarcón, Sandra; Ortiz, Macarena; Campos, Cristian; Vargas, Romina; Videla, Luis A.
Abstract : The DHA plus HT combined protocol prevents WAT alterations induced by a high-fat diet in mice. Main related mechanisms. Abstract : Background : Nutritional interventions are promising tools for the prevention of obesity. The n-3 long-chain polyunsaturated fatty acid (n-3 LCPUFA) docosahexaenoic acid (DHA) modulates immune and metabolic responses while the antioxidant hydroxytyrosol (HT) prevents oxidative stress (OS) in white adipose tissue (WAT). Objective : The DHA plus HT combined protocol prevents WAT alterations induced by a high-fat diet in mice. Main related mechanisms. Methods : Male C57BL/6J mice were fed a control diet (CD; 10% fat, 20% protein, and 70% carbohydrates) or a high fat diet (HFD) (60% fat, 20% protein, and 20% carbohydrates) for 12 weeks, without and with supplementation of DHA (50 mg kg −1 day −1 ), HT (5 mg kg −1 day −1 ) or both. Measurements of WAT metabolism include morphological parameters, DHA content in phospholipids (gas chromatography), lipogenesis, OS and inflammation markers, mitochondrial activity and gene expression of transcription factors SREBP-1c, PPAR-γ, NF-κB (p65) and Nrf2 (quantitative polymerase chain reaction and enzyme-linked immunosorbent assay). Results : The combined DHA and HT intervention attenuated obesity development, suppressing the HFD-induced inflammatory and lipogenic signals, increasing antioxidant defenses, and maintaining the phospholipid LCPUFA n-3 content and mitochondrial function in WAT. At the systemic level, the combined intervention also improved the regulation of glucose and adipokine homeostasis. Conclusion : The combined DHA and HT protocol appears to be an important nutritional strategy for the treatment of metabolic diseases, with abrogation of obesity-driven metabolic inflammation and recovery of a small-healthy adipocyte phenotype.